PENGARUH PENDIDIKAN GIZI TENTANG ANEMIA DENGAN MEDIA ANIMASI TERHADAP PENINGKATAN PENGETAHUAN GIZI REMAJA PUTRI DI SMPN 01 TASIKMADU KARANGANYAR - PERMATA, MEGA, Dr.Mutalazimah,SKM.,MKes, Pramudya Kurnia, STP, M.Agr (2015)
Background: Nutritional education is an attempt to make a person or group of people understand the importance of nutrition. Conveying messages of nutrition is very important to improve the nutritional status of the community through nutrition education. Provision of nutrition education about anemia in Junior High School is expected to increase the knowledge of anemia and attitude change in diet. Research Objectives: Knowing the effect of nutrition education using the knowledge of the media animation increase knowledge of the anemia on young women junior high school in SMPN 01 Tasikmadu Karanganyar. Research Methods: The method used in this study is Quasi experiment with the design of the study is one group pretest and post test design. The total sample of 40 subjects were selected by systematic random sampling of all students of class VIII. Results: This study showed that before the given nutrition education using animation media obtained an average value of 69.50 while the level of knowledge after the given nutrition education using animation media obtained an average value of 83.75. Obtained through Paired Sample Test p = 0.000 where p <0.05 then Ho is rejected. Conclusion: There is the influence in the knowledge of the anemia before and after nutrition education given by the animation media on young women junior high school in SMPN 01 Tasikmadu Karanganyar